Хронологія декрету на честь Протогена на ґрунті синхронізації епонімного календаря Ольвії - Ніколаєв, М.І. (Археологія, 2012)
Синхронізація епонімного календаря дозволила деталізувати соціально-політичну історію Ольвії ранньоелліністичного часу, зокрема запропонувати хронологічну модель подій декрету на честь Протогена. Почти два века не прекращается дискуссия относительно хронологии выдающегося лапидарного памятника античности — ольвийского декрета в честь Протогена Гиеросонтова (IOSPE, І2, № 32). Более того, раздаются голоса, что датировка этого документа, вероятно, никогда не будет уточнена. Тем временем, инструментарий археологической науки пополняется; в частности, на основании синхронизации (в первом приближении) эпонимного календаря Ольвии (IOSPE, І2, № 201) созданы основы ольвийской родовой просопографии ІV—I вв. до н. э., а традиционные методы датировки лапидарных надписей (палеографический, языковый, формульный) дополнил просопографический, по которому датировка надписей выполняется на базе хронологии персонажей этих надписей и/или их родственников (предков, современников, потомков). Таким образом, целью этой статьи было изучение хронологии декрета в честь Протогена на базе предлагаемого метода. The discussion on the chronology of the Olbian Decree in honour of Protogenes Hierosontou (IOSPE, І2, № 32), a wellknown Ancient Greek lapidary monument, lasts for almost two centuries. Furthermore, opinions appear that dating of this document probably will never be specified. Meanwhile, the instruments of archaeological science are enriched; for instance, based on synchronization (as a first approximation) of Olbian eponymous calendar (IOSPE, І2, № 201) there are created grounds for Olbian family prosopography from the 6th c. to the 1st c. BC, while the traditional methods of lapidary inscriptions dating (palaeographic, linguistic, and formula one) are supplemented by the prosopographical method, based on which the dating of inscriptions is made after the chronology of personages of these inscriptions and/or their relatives (ancestors, contemporaries, and descendants). Thus, the goal of this article was the study of chronology of the Decree in honour of Protogenes based on the presented method.